A REVIEW ON CONTROVERSIES AND CLINICAL ASPECTS OF PARIBHASHA SHARIRY - Chavan Shravani Prakash; Sharma Gopal B (AYUSHDHARA, 2020)
Sharir Rachana is an integrative branch of Ayurveda that studies the human body in its most minute form to an organized structural form. Sushruta, first carried out a detailed cadaveric study of the human body around 2000 yrs ago and laid the bedrock of Sharir Rachana Vigyan in his Samhita. Cadaveric studies thus helped the ancient seers explore many structures of human body and thus with the passing time this scientific branch evolved with a complex nomenclature of the various body parts. These nomenclatures and definitions of the basic bodily structures are compiled under the heading of Paribhasha Sharir. The knowledge of Paribhasha Sharir holds utmost importance in the field of surgery and medicine as well. However lack of social and technological advancements in the era when Ayurveda was encrypted by the sages, there emerged out various controversies over a particular structure. Acharyas have stated out individual opinions over a single structure that created a big confusion to the forth coming generations. With developments in recent times these confusions were gradually resolved keeping the original texts and definitions unaltered. Thus the present article is a framework that reviews the controversies and applied aspects of Paribhasha Sharir in Rachana Sharir Vigyan.